2002
DOI: 10.12968/bjon.2002.11.2.9309
|View full text |Cite
|
Sign up to set email alerts
|

Identifying important issues for people with Parkinson's disease

Abstract: This article identifies issues that are important for people with Parkinson's disease (PD). A review of the literature showed that information about PD commonly relates to anatomy and physiology, medication and activities of daily living. These categories were used to formulate statements on a questionnaire, which was distributed to members of the Parkinson's Disease Society within the East Midlands. The results demonstrated that those with PD wanted advice on maintaining their independence, the amount of move… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 10 publications
1
6
0
Order By: Relevance
“…This study showed that PD patients are under-informed about critical aspects of their care, as was found previously [ 18 , 26 , 27 ]. A qualitative study from New Zealand on unmet needs showed that PD patients wanted their physicians to offer more information about their condition [ 26 ].…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…This study showed that PD patients are under-informed about critical aspects of their care, as was found previously [ 18 , 26 , 27 ]. A qualitative study from New Zealand on unmet needs showed that PD patients wanted their physicians to offer more information about their condition [ 26 ].…”
Section: Discussionsupporting
confidence: 81%
“…A qualitative study from New Zealand on unmet needs showed that PD patients wanted their physicians to offer more information about their condition [ 26 ]. Moreover, a British study demonstrated that PD patients were poorly informed about medication and treatment options [ 27 ]. Application of the PCQ-PD in a large Dutch sample certified that patients were in need for information regarding alternative health therapies and treatment options of allied health professionals [ 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…In a survey of 120 people with Parkinson's disease, issues of self-management, such as knowing how to respond to changing symptom displays and when to seek medical help, were identified as issues of high importance (Hayes, 2002). Collaborative management involves patient and healthcare practitioners working together to identify and solve problems to promote the patient's health in daily life.…”
Section: Resultsmentioning
confidence: 99%
“…However, having good knowledge on medication and its effects has a positive effect on adherence [18,20,21]. Patients themselves have expressed a desire for more information from their HCPs [19,22,23], especially about the ADRs of a drug, as illustrated in a survey of more than 2000 respondents, where close to 80% wanted information on all possible side effects of a drug [24]. The knowledge of what to expect and how to deal with it increases confidence and was seen as an independent predictor of adherence [20].…”
Section: Discussionmentioning
confidence: 99%